The Rise and Fall of the Oil Nation Venezuela - Rossi, Carlos A. author. aut Link
XXVIII, 561 p. 138 illus., 124 illus. in color.
Keywords: This book explains why Venezuela is so rich in natural resources—it has been producing oil since 1922 and harbors the largest oil reserves in the world—and yet it is also a failed nation of class-divided citizens exhibiting deep poverty in a corrupt, incompetent state. Venezuela is a bipolar nation, where two marked poles in the society exist which have historical origins and are mutually exclusive. The book provides a critical analysis of Venezuela's history, economy and politics and explains the context and implications of the bipolar poles, known as the elite pole and the resentful pole. Both, it shows, have done serious harm to Venezuela’s prosperity. The author describes the vicious circle of oil wealth, corruption, inefficiency and world market dependency and gives recommendations for a better future.